Early Clinical and Radiological Outcomes of the Metaphyseally Fixed Totally Stabilized Knee Prosthesis in Primary Total Knee Arthroplasty - Hossain, Fahad; Konan, Sujith; Kayani, Babar; Kontoghiorghe, Christina; Barrack, Toby; Sami Haddad, Fares (The Journal of Knee Surgery, 2020)
The use of valgus–varus constrained (VVC) implant designs in primary total knee arthroplasty (TKA) is considered in situations of severe deformities, bone loss, and inadequate soft tissue balance. It is not known whether the use of such prosthesis designs may predispose to reduced function owing to its constraining design. The components are usually implanted with diaphyseal stem extensions to dissipate the increased forces. The totally stabilized (TS) implant is a contemporary VVC design with metaphyseal fixation only. It has a conforming articulation with increased rotational freedom compared with conventional VVC designs. The aim of this study was to assess whether the use of the contemporary TS implant with its metaphyseally fixed components would be associated with inferior outcomes compared with conventional standard primary posterior stabilized (PS) implants. We reviewed 38 consecutive complex primary TKAs performed using the metaphyseally fixed TS implant and 76 matched patients receiving primary PS TKA, at a minimum follow-up of 24 months. The mean follow-up was 61.1 months (24–102). Only patients with osteoarthritis were included. Clinical outcome was assessed using range of motion (ROM) and Oxford knee score (OKS). Radiographic assessment was performed using the femorotibial angle (FTA) at 6 weeks followed by assessment of bone–implant interface lucencies at final follow-up. There were no major early postoperative complications. The mean postoperative ROM in the TS and PS groups were 114.1 and 112.0, respectively. There was no difference in the mean ROM and OKS between the two groups. The mean FTA for patients in both groups was within 3° of the expected. There was no evidence of progressive lucencies or implant migration at final follow-up. The metaphyseally fixed TS knee design achieves comparable short-term functional outcomes when compared with conventional PS designs in primary knee arthroplasty. Long-term follow-up studies are required to assess survivorship.
Keywords: totally stabilized knee; valgus–varus constrained knee; complex primary TKA; functional outcomes